Identification of problems arising during manual handling of food packaging by older consumers in Poland. Issue 12 (13th September 2019) - Świda, Jarosław; Halagarda, Michał; Prusak, Anna; Popek, Stanisław
Abstract : The ageing population all over the world requires much greater attention than it receives from many businesses, including packaging industry. Therefore, it is essential to investigate the specific needs, requirements, and expectations of older consumers, particularly those related to the labelling and ergonomics, so as to shape the food packaging characteristics. In this way, consumers' satisfaction and hence the brand loyalty can be built. The aim of the study was to analyse the needs of older consumers related to food packaging handling and other corresponding issues, as well as to develop guidelines for food producers. The research consisted of two stages: a survey that covered a group of 600 consumers aged 60 and older in southern Poland and individual in‐depth interviews (IDIs) carried out among 60 people over the age of 60 in southern Poland. The outcomes of this consumer research indicated the need for changes in food packaging designed for older consumers, especially in consideration of the physical limitations for its handling before and after the product purchase. Food producers should also pay particular attention to the problems connected with packaging as a source of information. Moreover, they should make modifications in packaging ergonomics, especially in terms of size, shape, and opening and closing features. According to respondents, packaging material should be safe for health but not necessarily environmentally friendly. Abstract : The aim of the study was to analyse the needs of older consumers related to food packaging handling and other corresponding issues, as well as to develop guidelines for food producers. The research consisted of two stages: a survey that covered a group of 600 consumers aged 60 and older in southern Poland and individual in‐depth interviews (IDIs) carried out among 60 people over the age of 60 in southern Poland. The outcomes of this consumer research indicated the need for changes in food packaging designed for older consumers, especially in consideration of the physical limitations for its handling before and after the product purchase.